Workshop of Web Analytics and Google My Business as Digital Marketing Tools - Amar P. Natasuwarna (STMIK Pontianak, 2020)
Web analytics can raise online sales. Businesspeople take advantage provided by the Google platform named Google My Business to promote their products online. As part of the implementation of Community Service, a workshop was held in collaboration with SMK Negeri 5 Pontianak on the use of web analytics and Google My Business. The participants took part were 30 students of the Culinary Art Department. This workshop was seized to increase students’ knowledge and skills in using web analytics tools and Google My Business so that they who were already in business be able to utilize these skills on online selling. Web analytics -including the two most popular tools used by businesses, namely Ubersuggest and Google Trends- were introduced. During the introduction of Google My Business, students directly practiced the online registration and feature introduction. A questionnaire was used to find out the attainment of knowledge. The results showed an increase in students’ knowledge in the important terms of Ubersuggest, Google Trends, and Google My Business. Moreover, students are expecting to develop their learning in using web analytics and Google My Business after practicing what has been learned in this workshop. Supposing they run digital marketing, this knowledge is worth accelerating sales performance, as well as escalating visitor traffic of the student’s fan page.